2018
DOI: 10.1186/s12871-018-0622-5
|View full text |Cite
|
Sign up to set email alerts
|

Epidural anesthesia and cancer outcomes in bladder cancer patients: is it the technique or the medication? A matched-cohort analysis from a tertiary referral center

Abstract: BackgroundThe perioperative period can be a critical period with long-term implications on cancer-related outcomes. In this study, we evaluate the influence of regional anesthesia on cancer-specific outcomes in a radical cystectomy (RC) cohort of patients.MethodsWe performed a retrospective analysis of patients with clinically-nonmetastatic urothelial carcinoma of the bladder who underwent RC at our institution from 2008 to 2012. Patients were retrospectively registered and stratified based on two anesthetic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 28 publications
0
27
2
Order By: Relevance
“…In contrast, no benefit of PDA on overall survival or cancer recurrence was found in patients with colorectal [48], prostatic [49] or bladder cancer [8,50]. Evaluating patients with major abdominal surgery for cancer, further studies [8,26,27,45] could not observe any significant influence of anaesthetic technique on patients' outcome, either.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…In contrast, no benefit of PDA on overall survival or cancer recurrence was found in patients with colorectal [48], prostatic [49] or bladder cancer [8,50]. Evaluating patients with major abdominal surgery for cancer, further studies [8,26,27,45] could not observe any significant influence of anaesthetic technique on patients' outcome, either.…”
Section: Discussionmentioning
confidence: 86%
“…In contrast, no benefit of PDA on overall survival or cancer recurrence was found in patients with colorectal [48], prostatic [49] or bladder cancer [8,50]. Evaluating patients with major abdominal surgery for cancer, further studies [8,26,27,45] could not observe any significant influence of anaesthetic technique on patients' outcome, either. Yet, in these collectives, the patients had various surgical procedures including gastrectomy, pancreatectomy, colectomy, hepatectomy, cystectomy, nephrectomy or prostatectomy.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In recent years, the effect of intraoperative anesthetic management on long-term clinical outcome of cancer patients has become an interesting research topic. Several retrospective studies reported that local anesthesia, especially perioperative epidural analgesia, was related to better survival and a lower incidence of local recurrence or distant metastasis in cancer patients [5][6][7][18][19][20][21]. Tyler et al observed the association between use of epidural anesthesia during primary pancreatic cancer resection and improved survival among PDAC patients [9].…”
Section: Discussionmentioning
confidence: 99%
“…However, surgical intervention might impair cell-mediated immunity and activated circulating tumor cells implantation which leave patients susceptible to develop of postoperative recurrence or metastasis 3 , 4 . Multiple retrospective studies have shown that regional anesthesia improved patient outcome after surgery in bladder, breast and lung cancers 5 - 7 . In addition, regional anesthesia such as epidural anesthesia may blunt the pro-metastatic effect of surgical stress and inhibit tumor growth and metastasis, especially in high concentrations 8 .…”
Section: Introductionmentioning
confidence: 99%